Velocity specifity in early-phase sprint training - Kristensen, G. O.; van den Tillaar, R.; Ettema, G. (The Journal of Strength and Conditioning Research, 2006)
A comparison of resistance running, normal sprint running, and supramaximal running was performed. Nineteen young, generally well-trained subjects were divided into 3 training groups: resistance, normal, and supramaximal groups. Resistance and supramaximal training was done using a towing device, providing extra resistance or propulsion forces, resulting in running speed differences of about 3.3% (supramaximal) and 8.5% (resistance), compared to normal sprinting. The training period was 6 weeks, with 3 training sessions per week (5 sprint-runs over 22 m). Running times were measured using photocells, and average step length and cadence were recorded by digital video. A small (0.5%) but significant (p < 0.05) overall pre-post difference was found in running velocity, but the 3 groups changed differently over the running conditions. All individual subjects improved sprinting velocity most on the trained form, at 1-2% (p < 0.001), and thus, the principle of velocity specificity in sprint training was supported. This indicates that to obtain short-distance sprinting improvement in a short period of time, one may prefer normal sprinting over other training forms.